Readings in macroeconomics - Jenkinson, T (Oxford University Press, 1996)
Fifteen papers, published over the last decade in the Oxford Review of Economic Policy, several updated and revised, explore a variety of topics in macroeconomics. Papers discuss the role of fiscal policy in the 1990s; options for U.K. fiscal policy; monetary and exchange-rate policy in Britain and Europe; floating exchange rates in theory and practice; the case for stabilizing exchange rates; balance of payments and international economic integration; consumer expenditure; inflation policy; inflation and the U.K. labor market; wage determination and the changing role of institutions in advanced industrialized countries; explanations of unemployment; new approaches to economic growth; an international perspective on the macroeconomics of growth; productivity and competitiveness; and whether relative economic decline reversed itself under the Thatcher regime. Jenkinson is Managing Editor of the Oxford Review of Economic Policy and Fellow and Tutor in Economics at Keble College, Oxford University. Index.